Health information for the teenage years: what do they want to know? - J. Rolinson (Information Research: An International Electronic Journal)
What are the health Information needs of adolescents? What do they want to know? Sex 'n drugs 'n rock and roll? Reviewed are the information needs of adolescents within the educational setting, analyses of previous use and sources of Health Information and also the anticipated needs and preferred sources for the future. The changing need for Health Information from medical information to information relating to image and sexuality is reported. The restrictions of the educational system and the National Curriculum in teaching Health Information are identified, as are the differences in roles and responsibilities of the teachers who have a designated interest teaching Health Information.